Use of Board Game Media in Increasing Knowledge about Maintenance of Dental and Oral Hygiene in Class III A and III B Students of SDN Bendul Merisi in 2024 - INTAN DEWI SAPUTRI (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Debris is soft material from stuck food residue. It is known from the initial examination data on September 4 2023 that students had a debris index score of 1.9 in the bad category and not in accordance with WHO regulations, namely 0 – 1.6 in the good category. The problem of this research is the high debris index rate in students in classes III A and III B at SDN Bendul Merisi in 2024. This condition is caused by a lack of knowledge about maintaining dental and oral hygiene. The aim of this research is to find out the use of board game media in increasing knowledge about maintaining dental and oral hygiene. This type of research is descriptive research using pretest and posttest with the research target being 56 students in class III A and III B at SDN Bendul Merisi. The data collection method uses a questionnaire sheet. The results of the research were that students' knowledge before counseling was in the poor category, while students' knowledge after counseling was in the good category. So it can be concluded that there is an increase in knowledge from poor to good after counseling using board game media for students in class III A and III B at SDN Bendul Merisi in 2024.